Development of Android-based Interactive E-Booklet to Maximize Critical Thinking Skills and Student Learning Motivation - Tsani, Ghanius; Saptono, Sigit (Journal of Environmental and Science Education, 2023)
This study aims to develop android-based interactive e-booklet to describe the characteristics of interactive e-booklet, analyze the validity of interactive e-booklet, and analyze user responses. This research method is development research with research design referring to 4-D design (define, design, development, and disseminate) which is modified to 3-D or only reaches the development stage, because the research was conducted during a pandemic. The results of this study are Interactive E-booklet which have five characteristics, namely (a) self-instructional, (b) self contained, (c) user friendly, (d) can provide critical thinking skills training for students during the learning process and evaluation, and (e) can help maximize students' learning motivation. The Interactive E-Booklet was declared very valid to be used, this was in accordance with the assessment of the experts with a validity achievement of 91.67% for the media aspect and 92,5% for the material aspect. The Interactive E-Booklet got a very good response from teachers and students with an average percentage of 92.5% for teacher responses and 86.77% for student responses. Based on these results, it can be concluded that Interactive E-booklet can help maximize critical thinking skills and students' learning motivation.